ЗНАЧЕННЯ МІЖПРЕДМЕТНИХ ЗВ’ЯЗКІВ У ПРОЦЕСІ ФОРМУВАННЯ ПРОФЕСІЙНОЇ СПРЯМОВАНОСТІ МАЙБУТНІХ УЧИТЕЛІВ ПРИРОДНИЧИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2007)
The article is devoted to intersubject relations in school system as well as in the system of higher education in selecting the contests for special subjects as one of the didactic conditions of new teachers' professional orientation in teaching subjects’.